Precarious Housing: Catch Basin and Depository of the »Supernumeraries« of Neoliberal Capitalism (PROKLA. Journal of Critical Social Science, 2025)
This article examines the manifestations of socio-structural and additional symbolic marginalization as a result of living in precarious neighbourhoods. Based on the concepts of surplus population and territorial stigmatization, multidimensional devaluation processes are analysed using the example of three properties in the university city of Göttingen. In addition to an already deprived social situation of the residents, elements of a symbolic surplusification are revealed, which can be understood as an everyday cultural and (socio-)spatial extension of surplus theory.
Keywords: Precarious Housing; Stigmatization; Surplusification; Underclass; Supernumeraries